Dragon Tames the Mekong: China’s Normative Power in Transboundary Water Management - Naqsabandiyah, Ayu Heryati (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2025)
This study investigates China’s motivations for establishing the Lancang–Mekong Cooperation (LMC) through a normative lens, applying Amitav Acharya’s framework of norm subsidiarity. The research employs qualitative and desk review methods to examine China’s efforts to reshape transboundary river governance in the Mekong Region. Findings reveal that China’s refusal to join the Mekong River Commission (MRC) and its rejection of the UN Watercourses Convention (UNWC) are closely tied to its anti-Western sentiment and historical memory of the “Century of Humiliation.” By positioning the LMC as an alternative cooperative framework, China advances new norms that diverge from established international standards. These include asserting its role as the upstream and leading state, maintaining sustainability without hindering economic development, and emphasizing the principle of state sovereignty. Such norms stand in contrast to the obligations outlined in the UNWC and Mekong Agreement, which stress prior consultation, equitable use, and minimizing harm among riparian states. This study contributes to understanding China’s normative strategies in regional governance and offers insights into how emerging powers employ norm subsidiarity to influence international rules.